Long-term outcomes of post-acute sequelae of SARS-CoV-2 infection: a cohort study protocol - Zhang, Dongquan; Tong, Maolin; Dong, Xingwen; Zhang, Chutian; Yuan, Yuan; Wang, Xiaojun; Gao, Jing; Guo, Longfei (Frontiers in Public Health, 2025)
IntroductionPost-Acute Sequelae of SARS-CoV-2 Infection (PASC) presents a multifaceted interplay of demographic, clinical, environmental, and socioeconomic factors. Quantification at the individual level of these factors remains underexplored. Our study aims to address this knowledge gap by analyzing the long-term health implications of PASC, utilizing a comprehensive integration of spatiotemporal, clinical, environmental, and socioeconomic data.Methods and analysisThe study will enroll over 4,000 confirmed COVID-19 patients from Gansu Provincial Hospital, treated from December 2022 to May 2023, as the baseline. These patients are spread across 14 cities in Gansu Province, with geographic coordinates ranging from 92°13′E to 108°46′E and 32°31’N to 42°57’N. Follow-ups will be conducted via structured telephone interviews at 24, 36, and 48 months post-discharge, from 2024 to 2027, to assess PASC and long-term health outcomes. Participants will be categorized into three age groups: children and teenagers (birth to 18 years), adults (18–65 years), and the older adult (over 65 years). Environmental and socioeconomic data corresponding to each case are also integrated. The primary objective is to assess the persistence and long-term health outcomes of PASC symptoms. Secondary objectives focus on evaluating the acute infection phase, its progression, and the efficacy of medical management strategies in influencing PASC trajectories. Mixed-effects models will be utilized to evaluate the impact of various factors on PASC, while spatiotemporal analyses will explore the correlations between environmental and socioeconomic conditions and the diagnosis and recovery trajectories of PASC.Ethics and disseminationThe Gansu Provincial Hospital’s research ethics committee has approved this study protocol. Participation will be voluntary, with informed consent obtained from all participants. Study results will be published in peer-reviewed journals.Clinical trial registrationChiCTR2400091805.